2021
DOI: 10.3390/polym13234085
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Adding Heartwood Extractives from Acacia confusa on the Lightfastness Improvement of Refined Oriental Lacquer

Abstract: In this study, a renewable polymeric material, refined oriental lacquer (ROL), used as a wood protective coating, and the Acacia confusa Merr. heartwood extractive, which was added as a natural photostabilizer for improving the lightfastness of ROL, were investigated. The best extract conditions for preparing heartwood extractives and the most suitable amount of addition (0, 1, 3, 5, and 10 phr) were investigated. The lightfastness index including brightness difference (ΔL *), yellowness difference (ΔYI), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
(69 reference statements)
1
5
0
Order By: Relevance
“…This also specifies that the coating forms a layer between the UV radiations and the wood and protects the wood from lignin deterioration. This result is in agreement with recent findings where they found that extractives form a protective barrier against UV irradiation. ,,, …”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…This also specifies that the coating forms a layer between the UV radiations and the wood and protects the wood from lignin deterioration. This result is in agreement with recent findings where they found that extractives form a protective barrier against UV irradiation. ,,, …”
Section: Resultssupporting
confidence: 94%
“…The representative diagram is illustrated in Figure . The desirable anti-UV aging property can partly lessen the discoloration of dyed wood after UV irradiation. , The result indicated that the −C–H of the side chains degraded by photodegradation, and the peroxide, benzoquinone, and carbonyl groups formed. ,, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations